Promoting the use of technology assessment to improve health care in developing countries : report of a working group (Danish Hospital Institute CopenhagenDK, 1994)
Discusses the needs, opportunities and priorities. Suggests a collaborative approach and proposes general guidelines for orientation and training.
DC